Chinese Civil Code - The General Part - - Bu, Yuanshi, (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2021)
In modern times, the codification of the entire civil law has become a rare phenomenon. Nevertheless, the Chinese law-maker has decided to create the first Civil Code in the history of PRC and set out an ambitious timeline to achieve this goal. In the process of construction, the future Chinese Civil Code will principally follow the Pandectist System and, in particular, contain a General Part. On 15th March 2017, the General Part was enacted, as scheduled, in the form of a single statute for the time being. By 2020, the other books covering the law of personality, obligations, property law, family and estate law, should be codified as well. These books, together with the General Part, will form the future Civil Code. The purpose of this book is to provide a concise and in-depth practical guide to this new statute, namely the General Rules of Civil Law (GRCL). To this end, it seeks to deliver a general picture of the GRCL and to explore the important provisions in more detail. In addition, it strives to provide answers to the question of which laws apply in the case of conflict between the GRCL and other statutes. What is also equally important is to provide the readers with information about the origin of legal concepts in the GRCL and the process in which Chinese lawmakers decided to adopt or reject certain foreign legal concepts.